Teaching phonics and phonemic awareness in English Beginning reading - Bukhari Daud; Ummi Salamah (Universitas Syiah Kuala, 2016)
This is a library research study which investigates the roles of using phonics and phonemic awareness, the suggested stages in implementing them and finally the obstacles to using both phonics or phonemic awareness in a beginning reading classroom. There are some stages in implementing phonics, starting from vowel and consonant sounds in simple, familiar words and continuing on to digraphs, suffixes, diphthongs, letters with dual personalities, schwa sounds, silent letter digraphs and some letters with tricky sounds. Phonemic awareness should chronologically be taught with rhyming, manipulating, blending, segmenting and deleting. Both methods show considerable advantages for early reading learning such as instead of memorizing words, children can acquire decoding skills which can result in leading the children to improve their confidence in reading ESL, thus, they can then focus on the meaning of the reading and reading for enjoyment. Both methods are also able to help children understand that English has variations in spelling and pronunciation. Lastly, irregularity of English spellings, the lack of phonological knowledge of people working with children in early reading, the rising and falling moods of children whilst learning and the need for supportive parents hinder the implementation of either phonics or of phonemic awareness.